Taking a Common Concern Approach to Economic Inequality Implications for (Cooperative) Sovereignty over Corporate Taxation - D.Beyleveld, Alexander (World Trade Institute Advanced Studies, 2022)
Through the lens of cooperative sovereignty and the common concern of humankind concept, this book contemplates what kind of transnational corporate taxation system would be necessary for appropriately dealing with rising economic inequality within countries under conditions of contemporary globalisation.